Up to 206 Million People Reached and Over 5.4 Million Trained in Cardiopulmonary Resuscitation Worldwide: The 2019 International Liaison Committee on Resuscitation World Restart a Heart Initiative - Böttiger, Bernd W. (2020)
Sudden out-of-hospital cardiac arrest is the third leading cause of death in industrialized nations. Many of these lives could be saved if bystander cardiopulmonary resuscitation rates were better. "All citizens of the world can save a life-CHECK-CALL-COMPRESS." With these words, the International Liaison Committee on Resuscitation launched the 2019 global "World Restart a Heart" initiative to increase public awareness and improve the rates of bystander cardiopulmonary resuscitation and overall survival for millions of victims of cardiac arrest globally. All participating organizations were asked to train and to report the numbers of people trained and reached. Overall, social media impact and awareness reached up to 206 million people, and >5.4 million people were trained in cardiopulmonary resuscitation worldwide in 2019. Tool kits and information packs were circulated to 194 countries worldwide. Our simple and unified global message, "CHECK-CALL-COMPRESS," will save hundreds of thousands of lives worldwide and will further enable many policy makers around the world to take immediate and sustainable action in this most important healthcare issue and initiative.